(untitled) (International Journal of Food and Nutritional Sciences, 2022)
ABSTRACT Strength training or resistance training involves the performance of physical exercises that are designed to improve strength and endurance. It is often associated with the lifting of weights. It can also incorporate a variety of training techniques such as bodyweight exercises, isometrics, and plyometrics. The objective of the study is to find out the Effect of Strength Training on Selected Physical Fitness Variables among Sprinting performance on Athletes. Hypothesis: There may not be any significant difference between pre test and post test on selected physical fitness among springing Athletes in relation to strength training program. Methodology